Merencanakan dan Mengatur Program Pembelajaran Atletik di Sekolah - Eddy Purnomo (Jurnal Pendidikan Jasmani Indonesia, 2005)
Pursuant to observations and facts which the writer sees frequently in thisfield, there are still a lot of physical education teachers showing less professionalismin their jobs. Professionalism of a physical education teacher can be seen while goingto teach his students in the field, for example in the teaching preparation, the management of exercises to be taught, the time management, the teaching materials mastering,etcetera.The ability of planning an athletic learning material at school has a close relationshipwith the management of the program of the athletic learning: whether it is going well ornot, how the learning sequences are, and also how to manage appliances and facilitiesis, etcetera.To plan an athletic learning at school, a teacher of the physical education has to comprehend the characteristics of each athletic branch and how to arrange matters of athleticlearning in the physical education. Therefore, its management and its preparation arrangement are A. Foreplay Phase, B. Main Exercise Phase (a. Games/plays, b. MainExercise, consisted of the elementary and advanced techniques).Keyword: Planning, Managing, Athletic, and Physical Education